HUBUNGAN PENGETAHUAN IBU DENGAN PEMBERIAN ASI EKSKLUSIF - Wulaningtyas, Eko Sri; Wati, Susi Erna; Noeraini, Ardina Rezky (Jurnal EDUNursing, 2023)
Background: Breastmilk (ASI) is milk produced by humans for consumption by infants and is the main source of nutrition for infants who cannot digest solid food. What is meant by exclusive breastfeeding here is breastfeeding for 6 months without other additional foods such as formula milk, oranges, honey, tea water, water and solid foods such as bananas, papaya,milkporridge, biscuits, rice porridge, and the team from birth to baby. 6 months old. Purpose: To determine the relationship between maternal knowledge and exclusive breastfeeding in Ringinsari Village, Kediri Regency. Methods: The study design was descriptive correlative with a cross sectional approach. The sample of the study was taken with the purposive Sampling technique. The independent variable is Mother's Knowledge. The dependent variable is exclusive breastfeeding. Data collection using a questionnaire. Statistical test using the Chi Square Correlation test. Results: Most of the respondents in Ringinsari Village, Kediri Regency have good knowledge, namely 21 people (39,6%) from a total of 53 people. Half of the respondents who did not provide exclusive breastfeeding were 34 people (64,15%) from a total of 53 people. Conclusion: there is a relationship between maternal knowledge and exclusive breastfeeding. Keywords: Mother's Knowledge, Exclusive Breastfeeding